Effect Of Functional Resistance Training Vs Aerobics On Cardiometabolic Parameters In Obese Young Women - A M.P.T, Shajitha Banu.; M.P.T, Ponmathi.P; B PhD, Sathyaprabha.; N PhD , Venkatesh.; .M.G MS (OG), Dhanalakshmi; S M.P.T, Subhalakshmi. (Journal of Neonatal Surgery, 2025)
Aim & Background: Obesity is one of the major public health concerns as globally inactivity and obesity are on the rise. According to World Health Organization Obesity is defined as abnormal or excessive fat accumulation that presents a risk to health. Obesity is largely associated with a decrease in life expectancy and the effect of obesity is greater among younger adults. The aim of study aims to compare the Functional Resistance Training and aerobics on cardiometabolic parameters in obese young women. Methods: The study was conducted at Sri Ramachandra Institute of Higher Education and Research, Chennai. Subjects was divided into two groups by a pre-test measurement of HDL, LDL, TG, TC and FBG was taken. One group was trained with Functional Resistance Training (FRT), physical activity and diet advices while the other group received Aerobic Training (AT), physical activity and diet advices. The post-test measures were taken following six weeks of intervention. Results: There is no statistically significant difference between pretest and post-test measures of HDL, LDL, TG, TC and FBG values in both Functional Resistance Training and Aerobic training (p > 0.05). There was statistically significant difference between pre-test and two post-test measures of BMI and WHR in FRT (p < 0.05). when both the groups are compared there was no significant difference between then (p>0.05). Conclusion: This study shows no significant difference in effect of Functional Resistance Training over Aerobic training on cardiometabolic parameters in obese young women. Clinical Significance: FRT is found to be clinically effective in BMI and WHR, thus quite beneficial in improving obesity. Future studies with longer duration can bring a better understanding of Functional Resistance Training which the patient found comfortable to exercise for prolonged time and had less fatigue too. Clinical trial number: REF/2022/06/055810